Long-term effects of lumacaftor/ivacaftor on paranasal sinus abnormalities in children with cystic fibrosis detected with magnetic resonance imaging - Wucherpfennig, Lena; Wünnemann, Felix; Eichinger, Monika; Seitz, Angelika; Baumann, Ingo; Stahl, Mirjam; Gräber, Simon Y.; Zhao, Shengkai; Chung, Jaehi; Schenk, Jens-Peter; Alrajab, Abdulsattar; Kauczor, Hans-Ulrich; et al. (Frontiers in pharmacology, 2023)
Introduction: Chronic rhinosinusitis (CRS) usually presents with nasal congestion, rhinorrhea and anosmia impacts quality of life in cystic fibrosis (CF). Especially mucopyoceles pathognomonic for CRS in CF may cause complications such as spread of infection. Previous studies using magnetic resonance imaging (MRI) demonstrated early onset and progression of CRS from infancy to school age in patients with CF, and mid-term improvements of CRS in preschool and school-age children with CF treated with lumacaftor/ivacaftor for at least 2 months. However, long-term data on treatment effects on paranasal sinus abnomalities in preschool and school-age children with CF are lacking.Methods: 39 children with CF homozygous for F508del (mean age at baseline MRI 5.9 ± 3.0 years, range 1-12 years) underwent MRI before (MRI1) and about 7 months after starting lumacaftor/ivacaftor and then annually (median 3 follow-up MRI, range 1-4) (MRI2-4). MRI were evaluated using the previously evaluated CRS-MRI score with excellent inter-reader agreement. For intraindividual analysis ANOVA mixed-effects analysis including Geisser-Greenhouse correction and Fisher’s exact test, and for interindividual group analysis Mann-Whitney test were used.Results: The CRS-MRI sum score at baseline was similar in children starting lumacaftor/ivacaftor in school age and children starting therapy at preschool age (34.6 ± 5.2 vs.32.9 ± 7.8, p = 0.847). Mucopyoceles were the dominant abnormality in both, especially in maxillary sinus (65% and 55%, respectively). In children starting therapy in school age the CRS-MRI sum score decreased longitudinally from MRI1 to MRI2 (−2.1 ± 3.5, p < 0.05), MRI3 (−3.0 ± 3.7, p < 0.01) and MRI4 (−3.6 ± 4.7, p < 0.01), mainly due to a decrease in the mucopyoceles subscore (−1.0 ± 1.5, p = 0.059; −1.2 ± 2.0, p < 0.05; −1.6 ± 1.8, p < 0.01; and −2.6 ± 2.8, p = 0.417, respectively). In children starting lumacaftor/ivacaftor in preschool age, the CRS-MRI sum score remained stable under therapy over all three follow-up MRI (0.6 ± 3.3, p = 0.520; 2.4 ± 7.6, p = 0.994; 2.1 ± 10.5, p > 0.999 and −0.5 ± 0.5, p = 0.740; respectively).Conclusion: Longitudinal paranasal sinus MRI shows improvements in paranasal sinus abnormalities in children with CF starting lumacaftor/ivacaftor therapy at school age. Further, MRI detects a prevention of an increase in paranasal sinus abnormalities in children with CF starting lumacaftor/ivacaftor therapy at preschool age. Our data support the role of MRI for comprehensive non-invasive therapy and disease monitoring of paranasal sinus abnormalities in children with CF.
Gesehen am 07.06.2023